2015
DOI: 10.1210/en.2014-1718
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Treatment Prevents the Cardiomyopathy Observed in Obese Diabetic Male db/db Mice

Abstract: Oxytocin (OT) is involved in the regulation of energy metabolism and in the activation of cardioprotective mechanisms. We evaluated whether chronic treatment with OT could prevent the metabolic and cardiac abnormalities associated with diabetes and obesity using the db/db mice model. Four-week-old male db/db mice and their lean nondiabetic littermates (db/+) serving as controls were treated with OT (125 ng/kg · h) or saline vehicle for a period of 12 weeks. Compared with db/+ mice, the saline-treated db/db mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
112
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(133 citation statements)
references
References 56 publications
17
112
3
1
Order By: Relevance
“…Those reports also did not include body weight or total fat mass following diet exposure in either HFD-fed rats or age-matched chow-fed control rats (23) but instead focused on the effects of chronic subcutaneous infusions of oxytocin on changes of body weight gain and body composition relative to vehicle treatment. Consistent with other studies (23,73), oxytocin treatment limited fat mass while eliciting either no Values are means Ϯ SE; n ϭ 5-6/group. FGF-21, fibroblast growth factor-21; FFA, free fatty acids.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Those reports also did not include body weight or total fat mass following diet exposure in either HFD-fed rats or age-matched chow-fed control rats (23) but instead focused on the effects of chronic subcutaneous infusions of oxytocin on changes of body weight gain and body composition relative to vehicle treatment. Consistent with other studies (23,73), oxytocin treatment limited fat mass while eliciting either no Values are means Ϯ SE; n ϭ 5-6/group. FGF-21, fibroblast growth factor-21; FFA, free fatty acids.…”
Section: Discussionsupporting
confidence: 89%
“…One study reported that chronic subcutaneous administration of oxytocin, at a dose that reduced weight gain in obese db/db mice, also appeared to increase the number of uncoupling protein-1 (ϩ) cells in subcutaneous and visceral fat of obese db/db mice (73). Furthermore, Lawson and colleagues (48) demonstrated that oxytocin in amenorrheic athletes is positively correlated with resting energy expenditure as well as FGF-21 and irisin, two factors that induce the conversion of white adipose tissue to the "brite" or "beige" adipose tissue (14,28,98).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the strong anti-apoptosis effect of RSV in the AGE-BSA-treated endothelial cells, our results suggest RSV may be used an alternative therapy for the apoptosis-associated complications in type 2 diabetes, since such complications as diabetic retinopathy (Jiang et al, 2015), cardiomyopathy (Plante et al, 2015) and diabetic nephropathy (Hua et al, 2015). In addition, it is postulated that RSV over-expression positively regulates the insulin secretion and increases the sensitivity of endothelial cells to AGEs.…”
Section: Discussionmentioning
confidence: 70%